Pemphigus Vulgaris Combination Adjuvant Therapy of Systemic Corticosteroid with Sparing Agent Sodium Mycophenolate - Nopriyati; Cayadi Sidarta Antonius; Susanti Budiamal; Inda Astri Aryani (HM Publisher, 2020)
Pemphigus Vulgaris(PV) is an autoimmune disease characterized by vesicles and bullae on the skin and mucosa resulting from an autoantibody reaction to desmosomal adhesion molecules desmoglein (Dsg) 1 and 3, which function as strong adhesions between keratinocytes. Pemphigus Vulgarisis more common in the fifth and sixth decades of age. The lesions are fragile blisters on the mucosa and skin. Diagnosing PV requires anamnesis, physical examination,and investigations such as histopathologic examination and direct immunofluorescence. Therapy generally uses steroids. Adjuvant treatmentis given to reduce the side effects of corticosteroids. We reported a male, 59 years old, was treated with blisters that break easily into blisters on the head, face, chest, back, groin and buttocks accompanied by burning and itching. In the scalp, facial, anterior et posteriortrunk, inguinal,and gluteal regions, multiple erythematous maculeswere found with lenticular-plaqueshape; it waspartially confluentwith thick brown crustswhich werechallengingto remove. The histopathologicexamination found the presence of suprabasal bullae with lymphocyte inflammation cells. The patient was diagnosed with PV and treated with corticosteroids with the sparing agent mycophenolate sodium andshowed clinical improvement. The first-linetreatment for pemphigus Vulgarisis systemic corticosteroids. Adjuvant sparing agent therapy is given to reduce the side effects of corticosteroids. Sodium mycophenolate sparing agent was selected because ofitsminimum side effects. In systemic management, the dose of corticosteroid and sparing agent mycophenolate sodium was gradually decreased. The patient experienced initial remission after treatment